Implementation of Problem Based Learning Model Assisted by Electronic Student Worksheets to Improve Learning Outcomes and Learning Motivation on Reaction Rate Material - Manurung, Elisa; Pulungan, Ahmad Nasir; Sudrajat, Ajat; Amdayani, Susilawati; Roza, Destria (Journal of Science and Science Education, 2025)
Learning media serves to assist teachers in conveying information to students and can increase student learning motivation. This study aims to determine the application of the Problem Based Learning learning model assisted by E-LKPD to improve learning outcomes, learning motivation and the relationship between learning motivation and learning outcomes on the reaction rate material at Kartika 1-2 Medan Private High School. The type of research used is Quasy Experiment using pretest posttest. Sampling was done by purposive sampling. The sample consisted of one class, namely class XI IPA 4 as the experimental class (n = 30). Learning outcome data were processed using the Normalized Gain (N-Gain) test. The hypothesis was tested by linear regression and correlation test. The effectiveness of the Problem Based Learning learning model to improve learning outcomes and learning motivation on the reaction rate material is seen from the average posttest and pretest scores of 33.5 and 89.83, then the average N-gain value of 0.84 is included in the high category. The average value of students' initial and final learning motivation measured using a learning motivation questionnaire is 93.62, which is in the high category. These results indicate an increase in student learning outcomes after learning using the Problem Based Learning model assisted by E-LKPD. Hypothesis testing produces a value of rhit= 0.71 and rtabel = 0.36 at the significance level (  = 0.05) which shows that rhit > rtabel so it can be concluded that there is a significant relationship between learning outcomes and student learning motivation.